The strong coupled form-finding and optimization algorithm for optimization of reticulated structures. (February 2020) - Zhao, Zhongwei; Wu, Jinjia; Qin, Ying; Liang, Bing
Highlights: The strong coupled form-finding and optimization algorithm was proposed. The geometrical length of component can be optimized according to its internal force. The buckling capacity of the entire structures can be optimized during form-finding analysis. The buckling capacity of the entire structures can be significantly improved. Abstract: Reticulated shell structures are commonly adopted because of their long-span feature and novel appearance. These structures generally comprise slender beam members, which may cause the buckling of entire structures. A shape-finding method is proposed in this study to eliminate the bending moment while optimizing the member buckling capacity of reticulated shell structures. The proposed method (the strong coupling form-finding and optimization algorithm) can be utilized to optimize the geometrical length of each component. The effective length factor, sectional area, and moment of inertia can be accurately considered in the optimization analysis. Member length can be optimized according to the axial force and geometrical parameter. This study can systematically be adopted in the design, analysis, and optimization of reticulated shell structures. This work was conducted using a general finite element analysis program and can be easily mastered by engineering designers while avoiding tedious programming.